Analisis Penerapan Iso 45001 Dalam Pengangkutan Limbah B3 Di PT Pratama Karya Nugraha - Zarika, Athoriq Pratama Aufa; Ratnamurni, Elis Dwiana (Syntax Literate, 2025)
This study aims to analyze the implementation of ISO 45001:2018 as an occupational health and safety management system (OHSMS) standard in the transportation process of hazardous and toxic waste (B3) at PT Pratama Karya Nugraha using the Plan-Do-Check-Action (PDCA) approach. This research employed a qualitative method with data collected through interviews, observations, and documentation, and samples determined using purposive sampling. The findings reveal that the implementation of ISO 45001 has not been fully optimal, particularly in the Do, Check, and Act stages. In the Do stage, some workers were found not consistently wearing personal protective equipment (PPE), emergency response training was lacking, and adequate safety signs and warning systems were not in place. In the Check stage, regular occupational health monitoring had not been conducted, while in the Act stage, incident and nonconformity documentation was poorly managed. The study recommends enhancing OHS training and socialization, installing safety signs, conducting periodic health checks, strengthening documentation, and ensuring active management involvement in supervision to make ISO 45001 implementation more effective and supportive of operational safety.